Recent advances in gut microbiota metabolite regulation of hepatic pregnane X receptor - Lin, Tong; Chen, Yang; Liu, Linquan; Wu, Tiesong; Qian, Yan; Jin, Baofen (Frontiers in Immunology, 2025)
The pregnane X receptor (PXR), a key hepatic nuclear receptor, exhibits a highly plastic ligand-binding domain (LBD) that recognizes diverse endogenous and exogenous ligands, contributing to interindividual variations in xenobiotic metabolism and toxic responses. Emerging studies on the gut-liver axis reveal that microbiota metabolites regulate hepatic PXR through dual mechanisms: (1) Direct ligand-receptor interactions, where secondary bile acids (e.g., 3-keto LCA, DCA) and indole-3-propionic acid (IPA) bind PXR-LBD via hydrogen bonding to induce conformational changes, subsequently upregulating CYP3A4/ABCB1 expression while inhibiting NF-κB-mediated inflammation and modulating bile acid homeostasis through crosstalk with the farnesoid X receptor (FXR); and (2) Epigenetic reprogramming, wherein short-chain fatty acids (SCFAs) such as butyrate enhance PXR transcription by inhibiting histone deacetylase (HDAC) activity and promoting histone acetylation (e.g., at H3K9/K14 residues), thereby increasing promoter accessibility. This epigenetic mechanism contrasts with the direct ligand-binding pathway by acting indirectly through chromatin remodeling. Dysregulated PXR signaling underlies bile acid imbalance, mitochondrial dysfunction, and chemoresistance, driving clinical development of interventions including probiotic modulation of LCA/DCA balance, triptolide-mediated PXR activation, and structure-based PXR-targeted drug design. These findings highlight the microbiota-PXR axis as a critical determinant of drug response heterogeneity and a promising therapeutic target for metabolic liver disorders and refractory malignancies.